The anti-microbial defense of Drosophila: a paradigm for innate immunity - Hoffmann, Jules (Henry Stewart Talks, 2009)
The insect host defense is a multifaceted process, Systemic anti-microbial response in Drosophila, NF-kB: a central transactivator in immune responses, Gene cascade, The Toll pathway, Imd pathway mutants are sensitive to bacterial infections, Toll pathway mutants are sensitive to fungal infections, TLR family members and their ligands, The semmelweis (seml) mutation compromises the anti-gram-positive defense, Structural aspects of PGRPs, NF-kB activation by Toll and IMD in Drosophila, Investigating the response of Drosophila to virus infection, Response to RNA virus infections, Keeping parasite numbers low: role of the mosquito immune system, Losses and amplification of Plasmodium in A. gambiae, Cactus, ThioEster-containing Protein 1 (TEP1)